Quality appraisal of economic evaluations done on oral health preventive programs‐A systematic review. (20th April 2020) - Mariño, Rodrigo; Ravisankar, Gayatri; Zaror, Carlos
Abstract: Objectives: If economic evaluations are to be used by decision makers, such evidence has to be robust so that the relevant policy maker use them. This study was undertaken with the purpose of identifying economic evaluations done on oral health preventive programs and to assess the standard of economic evidence in this field. Methods: A systematic search was conducted using four major electronic databases in order to search for economic evaluations done on oral health preventive programs. This included economic evaluations that were published between January 1975 and May 2018 on preventive interventions for periodontal disease, oral cancer screening, and other common oral health conditions. To avoid duplications with previous studies, for dental caries interventions, this review included studies from April 2012 and May 2018. "Guidance to undertaking reviews in health care, " developed by York University, was used to assess the quality of reporting in the evaluations, using which strengths and shortcomings were identified. Results: A total of 2026 records were initially found. After title and abstract screening, and elimination by full text review, 33 relevant economic evaluations were identified. Majority of the economic evaluations included were conducted on dental caries prevention; a few were done on oral cancer screening, periodontal disease, and general preventive dentistry (health promotion, oral hygiene etc.). Conclusions: In comparison to the findings observed in previous reviews, there has been improvements in the quality of reporting in economic evaluations. Several areas still in need for improve were identified (e.g., productivity costs, currency and prices, and generalizability issues).